The Peru Approach against the COVID-19 Infodemic: Insights and Strategies - Alvarez-Risco, Aldo; Mejia, Christian R; Delgado-Zegarra, Jaime; Del-Aguila-Arcentales, Shyla; Arce-Esquivel, Arturo A; Valladares-Garrido, Mario J; Rosas Del Portal, Mauricio; Villegas, León F; Curioso, Walter H; Sekar, M Chandra; Yáñez, Jaime A (The American journal of tropical medicine and hygiene, 2020)
The COVID-19 epidemic has spawned an "infodemic," with excessive and unfounded information that hinders an appropriate public health response. This perspective describes a selection of COVID-19 fake news that originated in Peru and the government's response to this information. Unlike other countries, Peru was relatively successful in controlling the infodemic possibly because of the implementation of prison sentences for persons who created and shared fake news. We believe that similar actions by other countries in collaboration with social media companies may offer a solution to the infodemic problem.